Editor's Choice – Risk of Rupture and All Cause Mortality of Abdominal Aortic Ectasia: A Systematic Review and Meta-Analysis. (July 2022) - Shirasu, Takuro; Takagi, Hisato; Kuno, Toshiki; Yasuhara, Jun; Kent, Kenneth Craig; Tracci, Margaret C.; Clouse, William Darrin; Farivar, Behzad S.
Abstract : Objective: To clarify the natural history of abdominal aortic ectasia (AAE) measuring 25 – 29 mm in maximum diameter, and to determine the optimal follow up based on the growth, risk of rupture, and overall mortality of AAE. Data Sources: MEDLINE, Web of Science Core Collection, and Google Scholar. Review Methods: This was a systematic review and meta-analysis of AAE in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. MEDLINE, Web of Science Core Collection, and Google Scholar were searched, with the help of a health sciences librarian, up to 11 August 2021. Studies with longitudinal outcomes of AAE (prevalence, annual growth rate, aneurysmal enlargement, rupture, aneurysm related death, and all cause mortality) were included. Meta-analyses were conducted with a random effects model Results: Twelve studies describing a total of 8 369 patients were eligible. The prevalence at population based settings was 3.2% (95% confidence interval [CI] 2.4 – 4.0); annual growth rate was 0.82 mm/year (95% CI 0.20 – 1.45). The estimated risks of aortic diameters exceeding 30 mm and 55 mm in five years were 45.0% (95% CI 28.5 – 61.5) and 0.3% (95% CI 0 – 0.6) respectively, while those beyond five years were 70.2% (95% CI 46.9 – 93.6) and 5.2% (95% CI 2.2 – 8.2). The rates of rupture and aneurysm related death were minimal until five years (0.1% and 0.1%, respectively) and beyond (0.4% and 0.2%, respectively). Overall mortality was 7.5% (95% CI 3.9 – 11.0) and 17.3% (95% CI 9.5 – 25.1) up to and beyond five years. Overall mortality from three studies showed no statistical difference between AAE and aneurysms (hazard ratio 0.62, 95% CI 0.32 – 1.21; p  = .16). Cancer (35.0%) and cardiovascular diseases (31.9%) were major causes of death. Conclusion: AAE carries minimal risk of aneurysm related lethal events during the first five years, but a similar overall mortality risk as abdominal aortic aneurysm. Cancer and cardiovascular diseases are leading causes of death in patients with AAE.